Numerical Analysis of Eccentrically Loaded Cold-Formed Plain Channel Columns. (24th June 2014) - Nivethitha, A. P.; Vani, G.; Jayabalan, P.
Abstract : Finite element analysis of pinned cold-formed plain channel columns of different width-to-thickness ratios is presented in this paper. The study is focused not only on axially loaded columns, but also on eccentrically loaded columns. The general purpose finite element software ABAQUS 6.12 was used, and the force controlled loading was adopted. Geometric and material nonlinearities were incorporated in the finite element model. The ultimate loads are compared with the direct strength method (DSM) for axially loaded columns. Also, a parametric study is done by varying the length of the column and width of the unstiffened element. It is observed that the results correlate better with the DSM values for columns having unstiffened elements of lowerb f / t ratios. The change in ultimate load is studied only in ABAQUS, as the position of load moves towards the free edge and the supported edge of the unstiffened element. A parametric study is done by varying the nonuniform compression factor for the columns. It is observed that the ultimate load increases as the position of load moves towards the supported edge and it is influenced by theb f / t ratio of the unstiffened element.